MENSTRUAL CHARACTERISTICS AND PREVALENCE OFDYSMENORRHOEA AMONG FEMALE PHYSIOTHERAPYSTUDENTS (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Background: A common gynaecological problem encountered among female students is dysmenorrhoea, which alsoappears to be a leading cause of absenteeism from college. Hence arises a need to evaluate the menstrual characteristics andprevalence of dysmenorrhoea along with its severity among students.Materials and methodology: This cross-sectional study was conducted between March 2014 to July 2014 at SPBPhysiotherapy College, Surat, Western India. The study group included 133 female students. The data was collected bygeneral assessment form, questionnaires regarding menstrual characteristics and dysmenorrhoea, Visual analogue scale(VAS) and Verbal multidimensional scoring system (VMSS) for assessment of dysmenorrhoea severity. Percentages andChi-square test were used for statistical analyses.Results: The average age of the participants was 20.8 ± 1.8 years (range 17–23 years).Prevalence of dysmenorrhoea wasfound to be 71.2%.There was an association between dysmenorrhea and coffee consumption, choclate consumption,menstrual bleeding duration days, menstrual cycle regularity, family history of dysmenorrhoea, any gynaecological diseases(P < 0.05, for each one). Among dysmennorhic respondents, visual analog scale (VAS) for pain of dysmenorrhoea was 1-3(n=48), 4-7(n=19), 8-10 (n=22).Conclusion: Dysmenorrhoea is a very common problem among girls and it affects their quality of life. It can be bettermanaged by mental preparation and by appropriate change in lifestyle like regular physical exercise and with assurance tothe students. It is important to spread awareness about the causes and treatment of dysmenorrhoea to avoid undue sufferingscausing absenteeism from work and studies.